A comparative study of Rh and Ni coated microchannel reactor for steam methane reforming using CFD with detailed chemistry. (1st December 2015) - Cao, Chenxi; Zhang, Nian; Chen, Xin; Cheng, Yi
Abstract: Steam methane reforming (SMR) in microchannel reactors has great potential for low-cost, compact hydrogen production due to intensified heat and mass transfer features and an evident reduction of reaction time from seconds to milliseconds. In this work simulation studies of an integrated microchannel reactor were carried out by using a detailed CFD model with elementary reaction kinetics. The model predictions were quantitatively validated by experimental data. The numerical simulations showed the comparison of catalytic performances of Rh and Ni catalysts for SMR in two operating modes, namely, inner-heating and outer-heating. The results demonstrated that Ni catalyst can exhibit excellent performance comparable to Rh under certain conditions. In the outer-heating mode, Ni showed much higher activity for water gas shift (WGS), which led to a higher H2 /CO molar ratio in the products but more CO2 emission. In the inner-heating mode, during an initial stage of methane oxidation, complete oxidation of methane (COM) mainly happened on Ni, whereas partial oxidation of methane (POM) mainly occurred on Rh. The second stage was characterized by SMR and WGS, which then exhibited similar features as the outer-heating mode. Reaction path analysis showed that the surface C concentration on Rh in the inner-heating mode was lower than that in the outer-heating mode all along. The surface C concentration on Ni was very small in the initial stage of the inner-heating process, but strongly increased after O2 was consumed. Inner-heating operation is therefore preferred for reducing coking probability. Highlights: Catalytic performances of Ni and Rh for SMR in microchannel reactors were investigated. Reaction paths in inner- and outer-heating operations were analyzed. Two reaction stages were clearly identified for Ni and Rh in the inner-heating process. Rh is more suitable for the inner-heating operating mode in terms of coking probability. Ni catalyst can exhibit comparable performance to Rh under certain conditions.